Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I cannot see any steps to this problem! Surely the answer is obvious? Is there a particular law which is used to make this statement?

$$((Q \wedge ¬P) \vee (Q \wedge P)) = Q$$

share|cite|improve this question
Shouldn't it be $$((Q \wedge ¬P) \vee (Q \wedge P)) = Q$$? – Pedro Tamaroff May 7 '12 at 3:03
It's hard to say, because you haven't said what steps are allowed. For example, if you already know that $\vee$ distributes over $\wedge$, the thing is very simple: you factor out the $Q$ from the disjuncts, obtaining $(Q\wedge(P\vee\lnot P))=Q$, etc. – MJD May 7 '12 at 3:04
MarkDominus yes you are right, I can see the answer now. $$(Q \wedge (P \vee ¬P)) = Q$$ (Distributive Law) $$(Q \wedge T) = Q$$ (Excluded Middle) $$Q = Q$$ (Identity) – Danny Rancher May 7 '12 at 3:06

HINT: $$(Q\land\lnot P)\lor(Q\land P)\equiv Q\land(\lnot P\lor P)$$ by distributivity. Or of course you can simply use a truth table, if you're allowed to do so in this problem.

share|cite|improve this answer
@Mark: I'm sure that I didn't. Thanks for the quick catch. – Brian M. Scott May 7 '12 at 3:07

The shape of this makes me think of DeMorgan's Laws. You could start with $Q=Q \vee False$ But you could just do a truth table.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.